Biodiesel from various vegetables and tallow oils - Atiqah, Nafsun (2012)
This thesis deals with Biodiesel from various vegetables and tallow oils. The objective of this thesis is to produce the biodiesel from various feedstocks which are palm oil, corn oil, chicken fat oil, soybean oil, sunflower oil and waste cooking oil and also to analyze the physical properties each of biodiesel oil. The thesis describes the proper biodiesel extraction process, using proper catalyst and solvent in order to get the biodiesel physical properties standard of B100, ASTM6571. The studies of physical properties of biodiesel that are involved in this thesis consist of density, viscosity, cetanenumber, flash point, cloud and pour point and also acid value. As result, we observedthat palm oil has a nearest physical properties standard, ASTM6571. We comparedthese six different feedstock physical properties with some literature. As for therecommendation, conduct engine testing operating with various biodiesel and also perform one-dimensional simulation of internal combustion engine which operating with simulation such as GT-Power.